1996
DOI: 10.1021/jp9519225
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Reaction of Sulfur Dioxide on Alumina and Sodium-Impregnated Alumina

Abstract: The adsorption and oxidation of SO2 on alumina and sodium-impregnated alumina has been examined using thermogravimetric analysis and diffuse reflectance infrared Fourier transform spectroscopy. Sulfur dioxide chemisorbs initially at basic sites to form an adsorbed sulfite, which is quantitatively converted to sulfate on oxidation. It has been observed that at low coverages, ∼2.6 μmol/m2, sodium acts as a promoter for the formation of an adsorbed sulfite and sulfate which have structures similar to those of alu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 27 publications
6
73
0
Order By: Relevance
“…We have been applying spectroscopic techniques to identify and quantify surface adsorbing/ desorbing species responsible for sulfation and desulfation processes. The surface characterization provides insights about the underlying chemistry of the adsorption/desorption processes and the degradation mechanism (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The temperature and temporal probes of surface adsorbing species permit us to derive thermodynamic and kinetic parameters required for model development (13)(14)(15)(16)(17)(18).…”
Section: Resultsmentioning
confidence: 99%
“…We have been applying spectroscopic techniques to identify and quantify surface adsorbing/ desorbing species responsible for sulfation and desulfation processes. The surface characterization provides insights about the underlying chemistry of the adsorption/desorption processes and the degradation mechanism (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The temperature and temporal probes of surface adsorbing species permit us to derive thermodynamic and kinetic parameters required for model development (13)(14)(15)(16)(17)(18).…”
Section: Resultsmentioning
confidence: 99%
“…3a, spectrum ii) the 1368, 1102 signals become more visible which correspond to the 3 and 1 modes of surface sulfates on Al 2 O 3 , [60], respectively. Furthermore, the shoulder located at 1170 cm −1 which can be associated with bulk Al 2 (SO 4 ) 3 [56] starts to be more discernible. In addition, a relatively minor contribution from sulfate species that are interacting with the surface -OH groups which reveal typical signals at 1290 and 1080 cm −1 cannot be excluded [58].…”
Section: Pore Size Distributionmentioning
confidence: 91%
“…The formation of sulfates on alumina surface was considered in numerous former studies [56,57,60,68]. Typically, SO 2 binds to the acidic sites (i.e.…”
Section: Pore Size Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…3B). The surface HSO À 3 ð1242 cm À1 , Laniecki et al, 1987;Mitchell et al, 1996) and SO 2À 4 species (1363 cm À1 , Saur et al, 1986;Meunier and Ross, 2000;Goodman et al, 2001) were observed in addition to the surface HCO À 3 and HSCO À 2 species. It is also found that the peaks for surface HCO À 3 , HSO À 3 , HSCO2 À , and SO 2À 4 species increase in intensity with time in the soil.…”
Section: The Conversion Of Cos In the Lawn Soilmentioning
confidence: 96%